The Trading Game (T-Game) - John J. VanSickle; Amir Drusbosky (EDIS, 2003)
The Trading Game (T-Game) program is a tool to help students and industry practitioners learn more about trading commodities on the futures exchanges. The T-Game was designed by John VanSickle. This is EDIS document FE368, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published January 2003.